The Effect of Good Corporate Governance on Risk Management Disclosure in State-Owned Enterprises Listed on the Indonesia Stock Exchange (IDX) Period 2021-2024 - Saputri, Erna; Lamria Sagala; Duma Rahel Situmorang; Dompak Pasaribu (Universitas Methodist Indonesia, 2026)
This investigation was undertaken to test and analyze the effect of Good Corporate Governance on risk management information disclosure in state-owned companies registered on the Indonesia Stock Exchange. The sampling method used purposive sampling from an entire population of 24 state-owned enterprises, where all 24 companies served as research samples with data collected via www.idx.co.id. The research adopted a quantitative methodology employing multiple linear regression analysis as the analytical technique. Research outcomes reveal that partially, the board of commissioners exerts a positive yet statistically insignificant effect on risk management disclosure. Conversely, the audit committee exhibits a positive and statistically significant influence on risk management disclosure. Meanwhile, institutional ownership demonstrates a negative and non-significant impact on risk management information disclosure. Concurrently, all three independent variables namely the board of commissioners, audit committee, and institutional ownership display a significant collective influence on risk management disclosure. According to the coefficient of determination assessment, the board of commissioners, audit committee, and institutional ownership variables account for 31.5% of the variance in risk management disclosure, whereas the remaining 68.5% is attributable to other variables not incorporated in this study's regression framework.